Online sexual crimes, offenders, and victims: theory, research, and practice - Paquette, Sarah (Routledge studies in criminal behaviour, 2025)
"Adopting a multidisciplinary perspective, this volume explores contemporary knowledge regarding the online sexual exploitation of children and adolescents, and challenges prevailing myths perpetuated by society and the media concerning this form of violence, the offenders, and their victims. Drawing on a wealth of data collected from real cases in Quebec, the book introduces readers to explanatory models of online offending and victimization, the criminal trajectories and characteristics of online offenses, the individual attributes of offenders and victims, issues pertaining to virtual identities and anonymity preservation techniques, and considerations for prevention and intervention practices. Online Sexual Crimes, Offenders, and Victims will be of interest to students, researchers and professionals in the fields of criminal justice and public health, including criminologists, psychologists, psychiatrists, psychotherapists, social workers, police investigators, probation officers, magistrates, and lawyers"-- Provided by publisher